#TITLE_ALTERNATIVE# - PALUPI , KARINA
PT XYZ is an integrated palm-based consumer company. Palm tree is a main capital for PT XYZ. It's important for PT XYZ to have healthy palm tree so that can be productive in yielding fruit bunch which is source of palm oil. Like other life creature, palm tree must be given nutrition to reach optimal growth. The nutrition is found in various type of fertilizer. Therefore fertilizer is become a raw material for PT XYZ. Because of PT XYZ has many plantation, the requirement of fertilizer also has a big amount. With high amount and various kind of fertilizer requirement, a good arrangement is necessary so that would not happened excess or lacking to fulfill requirement for each type of palm tree. In procurement process of fertilizer there are several party involved. From research division named X, field operational, warehouses, central procurement, central finance, and supplier. Basically there are four main activities in procurement process of fertilizer, which are requirement planning, ordering, delivery and receipt, and fertilizer application. Requirement planning is process in order to know the requirement and amount of order. Ordering is process where PT XYZ choose the appropriate supplier and doing order based on result of requirement planning. Delivery and receiving are shipment process by the supplier and received by estate warehouses. Fertilizer application is manuring process, which has an influence to the following Procurement process. The primary activities can be shown as the business process of procurement process of fertilizer. Then, the business process is also described the root cause of problem happened. There are two main problems of procurement process: shortage and overage inventory, and delay on delivery. The ideas to solve problems of shortage and overage inventory are by doing 2-stages order, where in current condition PT XYZ applied single order system. By doing 2-stages order PT XYZ can minimize inaccuracy of order so that would be minimize the shortage and overage inventory. To solve problems of delay in delivery process is by giving a penalty as a punishment to the supplier and make proactive system to control delivery process. Penalty is given if the supplier were late in deliver the fertilizer. Besides, in order to avoid the delay in delivery PT XYZ can applied proactive system such as Early Warning System to monitoring delivery process from supplier's origin country up to estate warehouses. Therefore PT XYZ fulfill their requirement of fertilizer in correct amount, in proper condition, to place where fertilizer is required, on time when it's required and with lowest total cost.